Relationship of thymic area with clinical-epidemiological variables and values of T-lymphocyte subpopulations in peripheral blood of children with recurrent infections - Francisco Sotomayor Lugo; Yaíma Zúñiga Rosales; Oliver Pérez Martín; Evelyn Hernández Reyes; Evelyn M. Antiguas Valdés; Hermes Fundora Hernández; Katia Rodríguez Guitiérrez; Yaima Matas González; Imilla Casado Hernández; Carlos Agustín Villegas Valverde; Bárbara Torres Rives; Lázara Minerva Tam Rey; et al. (SpringerOpen, 2024)
Abstract Background Recurrent infections in childhood are the main cause of remission to the immunology service. T lymphocytes generated in the thymus are essential for fighting infection, making the thymus area an important predictor of the immune system's competence. This study aimed to identify the possible relationship of the thymic area with clinical-epidemiological variables and values of subpopulations of T lymphocytes in the peripheral blood of children with recurrent infections. Methods We conducted applied research using a transversal analytical design at the National Medical Genetics Center (Havana, Cuba), from January to August 2022. The study covered 73 children of which we analyzed clinical-epidemiological variables and the size of the thymus through ultrasound. Furthermore, we determined the relative and absolute values of the subpopulations of T cells using flow cytometry. Results Of the children studied, 65.8% had thymic hypoplasia. The children who breastfed for less than 6 months showed four times the risk of developing moderate-severe thymus hypoplasia (OR = 3.90, 95% CI: 1.21-12.61). A direct relationship was found between the area of the thymus and the child's size (r = 0.238, p = 0.043) and weight (r = 0.233, p = 0.047). The relative values of CD3+ T lymphocytes decreased in the cases of mild hypoplasia (p = 0.018) and moderate-severe hypoplasia (p = 0.049). The thymus area was associated with the absolute cell count of CD8+ effector memory T cells (rs = −0.263, p = 0.024) and of the central memory T cells (r = −0.283, p = 0.015). Conclusions Breastfeeding for less than 6 months, as well as the weight and size of the child, are related to their thymus area. The subpopulation values of T lymphocytes detected suggest that patients with thymic hypoplasia develop a contraction of CD3+ T cells, which can make them more vulnerable to infectious processes. This finding was combined with an expansion of the memory compartments of the subpopulations of CD8+ T cells, suggesting a greater susceptibility to intracellular viral and bacterial infections in these cases.